Food Security Strategies of Farmworker Households in Pa’batangan Village, Takalar Regency - Aulia Nur Fadilah; Idham Irwansyah Idrus; Ulfa Utami Mappe (Jurnal Sosiologi Nusantara, 2026)
Food security is a fundamental human right, yet agricultural workers in rural areas remain vulnerable due to structural limitations and economic instability. This study employs a qualitative, descriptive approach. This research employed a qualitative descriptive design. The data collection instruments and procedures used included in-depth interviews, observation, and documentation. A total of 8 informants working as farm laborers were interviewed to understand their perspectives and life experiences regarding livelihood uncertainty. Data analysis was conducted using qualitative descriptive methods based on the Theory of Sustainable Livelihoods proposed by Chambers and Conway and further developed by Scoones, which emphasizes the interrelationship between livelihood assets, household strategies, and the context of vulnerability. The research findings indicate that: (1) the food security of farmworker households is driven by several factors, including food availability, economic access, income diversification, the role of government social assistance, and land management. Meanwhile, inhibiting factors include dependence on seasons and weather, limited economic access to food, lack of land ownership, and limited alternative employment. (2) To survive, farmworker households employ adaptive strategies. These strategies include adjusting consumption patterns by reducing the types and quantities of food, managing food reserves from harvests, changing economic behavior during crises through saving and seeking additional work, dividing roles within the household—particularly women’s roles in managing consumption and finances—and leveraging social networks with family and neighbors as sources of social support. In conclusion, farmworker households maintain food security through adaptive livelihood strategies that optimize available assets, diversify income, and strengthen social support networks despite facing significant structural and seasonal constraints.